Evaluation of variability and principal component analysis in segregating populations of groundnut (Arachis hypogaea L.) - Vishnupraba, R Sangeetha; Viswanathan, PL; Manonmani, S; Rajendran, L; Selvakumar, T (Plant Science Today, 2025)
Groundnut is a favourable and profitable crop for resource-poor farmers in Africa and Asia, both for edible oil production and direct consumption. There is significant potential to breed high-yielding, better-quality groundnut cultivars by generating new variations through artificial techniques. In this study, the F2 generations of the crosses CO 7 × Chico and ICGV 07222 × Chico was analysed to assess the variability created through artificial hybridization in groundnut. The various yield and yield-related traits were analysed to estimate genetic parameters, skewness, kurtosis and subjected to principal component analysis (PCA). The variability study of the F2 population from both crosses revealed significant variations for the traits under study. The traits “days to accumulation of 25 flowers” and “shelling %” showed low GCV (genotypic coefficient of variation) and PCV (phenotypic coefficient of variation) in both populations. Most traits exhibited moderate to high heritability and genetic advance, whereas “days to accumulation of 25 flowers” and “maturity duration” had moderate heritability and low genetic advance. Only shelling % had low estimates of heritability and genetic advances. Tests for skewness and kurtosis revealed that both F2 population did not follow a normal distribution. The traits “days to maturity”, “shelling %”, “kernel yield,” and “hundred kernel weight” displayed significant positive skewness. The traits “days to accumulation of 25 flowers”, “number of matured pods”, “height of main axis”, “shelling %”, “hundred pods” and “hundred kernel weight” and “pod yield” showed platy- kurtosis, while “Kernel yield” displayed lepto-kurtosis in both populations. The first principal component explained 37 % and 32 % of the total variance in the 2 F2 populations respectively, with a focus on yield-related traits. The PCA biplot effectively clustered the genotypes based on the 10 different traits studied and clearly, grouped the population based on maturity duration. Thus, hybridization created significant variation in groundnut for all yield-related traits and yield, except for “days to maturity”. The traits require further enhancement using additional sources and could be improved through intense selection.